Consumer willingness to pay for green express packaging in e-commerce: an eye-tracking experiment analysis - Yan, Zhenshui; Wang, Tianbo; Song, Zizheng; Liu, Jiarui; Lyu, Wei (Frontiers in Psychology, 2025)
With the rapid development of e-commerce, packaging waste has surged, making green express packaging (GEP) a key component of sustainable logistics promotion. This study investigates the influence of product types (search goods vs. experienced goods), price sensitivity, and environmental awareness on consumers’ willingness to pay for GEP. Data were collected through a combination of questionnaire surveys and eye-tracking experiments, and analyzed by SPSS 27.0. The results show that consumers with higher environmental awareness demonstrate a greater willingness to pay for GEP premiums, particularly when purchasing experienced products. However, price plays a significant restrictive role in the choice of green express. Eye-tracking data reveal that green express option attracts more visual attention than traditional one. Although higher premiums reduce willingness to pay, they do not diminish visual attention. E-commerce platforms and express delivery companies should consider product type, consumers’ environmental awareness, and price sensitivity when formulating pricing strategies for green packaging to optimize consumers’ willingness to pay.